FERTILITY PRESERVATION: ADVANCES IN CRYOBIOLOGY, REGENERATIVE, AND NANOMEDICINE STRATEGIES – AN OVERVIEW : EMERGING TRENDS IN FERTILITY PRESERVATION - SELVAKUMAR M; DHANASEKAR J; SUDHAMANI T; DHANALAKSHMI M; LATHAMANI L; NANDHAKUMARAN S; SNEHAL DASHARATH PAWAR (The Bioscan, 2026)
The need to preserve fertility has now become a fundamental part of reproductive medicine due to the developments of cryobiology, regenerative medicine, nanomedicine and new biotechnologies. Optimised cryopreservation protocols can improve the viability and preservation properties of gametes and gonadal tissues, and nanotechnology can be used to target the delivery of protective factors and provide real-time monitoring of the reproductive organs. Decellularised scaffolds, 3D bioprinting, and stem cell therapy are regenerative techniques that offer biomimetic platforms that aid in vitro folliculogenesis, spermatogenesis, and tissue regeneration. New biotechnological methods, including CRISPR-based gene editing and in vitro gametogenesis, have the potential to fix genetic infertility and increase the resilience of the germline, but ethical, legal, and societal issues are of high concern. Artificial intelligence and machine learning also maximise fertility by foretelling gamete and embryo quality, personalised treatment direction, and better assisted reproductive technology success rates. The pediatric, adolescent, and transgender populations demand particular attention, and their strategies should consider the development stage, hormone treatment, and specific clinical requirements. Future studies must focus on the following: longitudinal studies, standardisation of technology, translational pathways so as to ensure safety, reproducibility and fair access. The combination of these multidisciplinary innovations alongside patient-centred and ethically- driven solutions can be used to redefine the concept of fertility preservation through the provision of safe, effective, and personalised solutions to individuals at risk of reproductive compromise.